2021
DOI: 10.3390/polym13060972
|View full text |Cite
|
Sign up to set email alerts
|

Tough Hydrogels Based on Maleic Anhydride, Bulk Properties Study and Microfiber Formation by Electrospinning

Abstract: Hydrogels present a great number of advantages, such as their swelling capacity or their capability to mimic tissues, which make them very interesting biomaterials. However, one of their main disadvantages is their lack of good mechanical properties, which could limit some of their applications. Several strategies have been carried out to develop hydrogels with enhanced mechanical properties, but many of the suggested synthetic pathways to improve this property are expensive and time consuming. In this work, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The mechanical properties of nanofiber membrane wound dressings are crucial for maintaining stability and integrity under external pressures and stretching, thereby protecting wounds and promoting wound healing [41,42]. Mechanical property experiments were conducted on Janus nanofiber membranes to assess their performance in this regard (Figure 4a).…”
Section: Mechanical Properties Of Janus Nanofibersmentioning
confidence: 99%
“…The mechanical properties of nanofiber membrane wound dressings are crucial for maintaining stability and integrity under external pressures and stretching, thereby protecting wounds and promoting wound healing [41,42]. Mechanical property experiments were conducted on Janus nanofiber membranes to assess their performance in this regard (Figure 4a).…”
Section: Mechanical Properties Of Janus Nanofibersmentioning
confidence: 99%
“…These products were then copolymerized with styrene and vinyl acetate monomers to produce random terpolymers, namely; poly(dioctadecanoyl maleate-co-styrene-co-vinyl acetate) and poly(octadecanoyl maleate-co-styrene-co-vinyl acetate). Crosslinking maleic anhydride copolymers by bifunctional-group polymer was established by Bettahar et al [12] who synthesized some mechanically stable hydrogels by thermally grafted poly(ethylene-alt-maleic anhydride) and poly(methyl vinyl ether-alt-maleic anhydride) with poly(ethylene glycol). Maleic anhydride copolymers are also found as anionic polyelectrolytes in poly(stilbene-co-maleic anhydride) and opening ring by ionic substance can impart charge densities to the copolymer [13].…”
Section: Introductionmentioning
confidence: 99%
“…The thermal stability of the polymers was also studied using TGA. It was observed that some of the copolymer samples contained residual water, as evidenced from weight losses below 100 C. As is shown in the TGA data (Figure 5.9), maximum thermal degradation of PEG2000 and PEG5000 was observed to occur at about 420 C, whereas degradation of the shorter chain PEG550 was observed to occur at approximately 300 C. Degradation of the pure Octa and IB backbone shown two peaks at 280 C (which is related to maleic anhydride group (Bettahar et al, 2021;Martínez, Uribe, and Olea, 2005;Kumar et al, 2016)…”
Section: Synthesis Of Graft Copolymers Derived From Polymentioning
confidence: 71%